Baselines for Assessment of Choice Programs - Hill, Paul T.; Guin, Kacey (Education Policy Analysis Archives, 2003)
Critics of choice argue that it will allow alert and aggressive parents to get the best of everything for their children, leaving poor and minority children concentrated in the worst schools. (Note 1) But choice is not the only mechanism whereby this occurs. Alert and aggressive parents work the bureaucracy to get the best for their children. Thus, choice programs should be compared against the real performance of the current public education system, not its idealized aspirations.